Epidemiology of birth defects based on a birth defects surveillance system in southwestern China and the associated risk factors - Peng, Zhenren; Wei, Jie; Chen, Biyan; Huang, Xiuning; Song, Pengshu; Liang, Lifang; He, Jiajia; Feng, Baoying; Que, Ting; Qin, Jie; Xie, Yu'an; Qiu, Xiaoxia; et al. (Frontiers in Pediatrics, 2023)
Background Birth defects (BDs) are associated with many potential risk factors, and its causes are complex. Objectives This study aimed to explore the epidemiological characteristics of BDs in Guangxi of China and the associated risk factors of BDs. Methods BDs data of perinatal infants (PIs) were obtained from the Guangxi birth defects monitoring network between 2016 and 2020. Univariate Poisson regression was used to calculate the prevalence-rate ratios (PRR) to explore the changing trends of BDs prevalence by year and the correlation between the regarding of characteristics of BDs (including infant gender, maternal age, and quarter) and BDs. Clinical characteristics of PIs with BDs and general characteristics of their mothers were documented, and Spearman correlation analysis was used to explore the potential associated risk factors of BDs. Results Between 2016 and 2020, 44,146 PIs with BDs were monitored, with an overall BDs prevalence of 121.71 (95% CI: 120.58–122.84) per 10,000 PIs, showing a significant increase trend (PRR = 1.116, 95% CI: 1.108–1.123), especially the prevalence of congenital heart defects (CHDs) that most significantly increased (PRR = 1.300, 95% CI: 1.283–1.318). The 10 most common BDs were CHDs, polydactyly, congenital talipes equinovarus, other malformation of external ear, syndactyly, hypospadias, cleft lip with cleft palate, cleft lip, hemoglobin Bart's hydrops fetalis syndrome (BHFS), and congenital atresia of the rectum and anus. BDs were positively correlated with pregnant women's age (R = 0.732, P < 0.01) and education level (R = 0.586, P < 0.05) and having pre-gestational diabetes mellitus (PGDM)/gestational diabetes mellitus (GDM) (R = 0.711, P < 0.01), while when the pregnant women had a family history of a dead fetus (R = −0.536, P < 0.05) and a birth of a fetus with BDs (R = −0.528, P < 0.05) were negatively correlated with BDs. Conclusion A significant increase in the prevalence of BDs was detected between 2016 and 2020 in Guangxi, especially the prevalence of CHDs that most significantly increased. Older maternal age, higher maternal education level, and having PGDM before pregnancy or GDM in early pregnancy were the risk factors for BDs.